DEVELOPMENT OF STUDENTS' UNDERSTANDING OF EXPONENTIAL BASED ON COGNITIVE STYLE - Eka Novi Arisandi; Yusuf Fuad (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2019)
Abstrak ” Pemahaman adalah faktor penting dalam pembelajaran matematika. Salah satu teori tentang pemahaman adalah Teori Pirie-Kieren. Teori Pirie-Kieren menjelaskan tentang pertumbuhan pemahaman. Faktor internal yang mempengaruhi pemahaman siswa adalah gaya kognitif. Ada berbagai jenis gaya kognitif, salah satunya adalah gaya kognitif pemahaman konsep berbasis waktu, yaitu gaya kognitif Reflektif-Impulsif. Tujuan dari penelitian ini adalah untuk menggambarkan tingkat pemahaman siswa SMP tentang perpangkatan berdasarkan teori Pirie-Kieren dan gaya kognitif reflektif-impulsif. Penelitian ini menggunakan Matching Familiar Figure Test (MFFT), Tes Kemampuan Matematika (TKM) dan Tes Pemahaman Materi Perpangkatan (TPMP) dan juga pedoman wawancara untuk menggambarkan tingkat pemahaman siswa tentang Perpangkatan berdasarkan teori Pirie-Kieren. Subjek penelitian adalah siswa kelas dua. Berdasarkan hasil pemberian TPMP diperoleh 7 siswa dengan gaya kognitif reflektif dan 10 siswa dengan gaya kognitif impulsif. Berdasarkan hasil pemberian TKM, dari 7 siswa dengan gaya kognitif reflektif diperoleh 4 siswa dengan kemampuan matematika tinggi dan 2 siswa dengan kemampuan matematika rendah. Pada gaya kognitif impulsif, 10 siswa memperoleh 3 siswa dengan kemampuan matematika tinggi, seorang siswa dengan kemampuan matematika sedang dan 6 siswa dengan kemampuan matematika rendah. Selanjutnya, dengan mempertimbangkan nilai hasil TPMP dan kesukarelaan siswa, dipilih 4 subjek penelitian dengan kemampuan matematika tinggi, ada 2 subjek dengan gaya kognitif reflektif dan 2 subjek dengan gaya kognitif impulsif. Hasil penelitian menunjukkan bahwa tingkat pemahaman siswa SMP tentang perpangkatan berdasarkan teori Pirie-Kieren dan gaya kognitif reflektifimpulsif adalah, (1) siswa dengan gaya kognitif reflektif dapat mencapai tingkat observing padalevel pemahaman oleh Teori Pirie-Kieren dan (2) siswa dengan gaya kognitif impulsif juga mencapai level observing pada level pemahaman oleh Teori Pirie-Kieren.Kata kunci: Pemahaman, Perpangkatan, Teori Pirie-Kirien, Reflektif-Impulsif Abstract ” Understanding is an important factor in mathematics teaching learning. One of theories about understanding is Pirie-Kierens Theory. Pirie-Kieren's theories explain about growth of understanding. Internal factors that influence students' understanding include cognitive style. There are various types of cognitive styles, one of which is a time-based cognitive style of concept understanding, namely the Reflective-Impulsive cognitive style. The purpose of this study is to describe the level of junior high school students' understanding of the exponential based on of Pirie-Kieren's theory and reflective-impulsive cognitive style. This research used Matching Familiar Figure Test (MFFT), Mathematics Ability Test (TKM) and Departure Material Understanding Test (TPMP) and also interview guidelines to describe the level of students' understanding of exponential based on Pirie-Kieren's theory. The subjects of the study were students in second grade. Based on the results of giving TPMP obtained 7 students with reflective cognitive style and 10 students with impulsive cognitive style. Based on the results of giving TKM, from 7 students with reflective cognitive styles obtained 4 students with high mathematical abilities and 2 students with low mathematical abilities. In impulsive cognitive style, 10 students obtained 3 students with high mathematical ability, a student with moderate mathematical ability and 6 students with low mathematical ability. Furthermore, taking into account the value of the results of TPMP and students' willingness to choose 4 subjects with high mathematical ability, there are 2 subjects with reflective cognitive style and 2 subjects with impulsive cognitive style. The results showed that the level of junior high school students' understanding of the material in terms of Pirie-Kieren's theory and reflective-impulsive cognitive style were, (1) students with reflective cognitive style could reach the observing level at the level of understanding of Pirie-Kieren's theory and (2) students with impulsive cognitive style can reach the level of observing at the level of understanding of the Pirie-Kieren theory.Keywords: Understanding, Exponential, Pirie-Kierens Theory, Reflective-Impulsive.